Hubungan Pola Makan Dengan Pengendalian Gula Darah Pada Lansia Penderita Diabetes Melitus Tipe 2 Di Puskesmas Belimbing Tahun 2025 - Linda Handayuni; Darmawan Saputri, Reja (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2025)
Factors that influence blood sugar levels include genetics, obesity, diet, age, and physical activity. An irregular diet is one of the leading factors contributing to uncontrolled blood sugar levels. This study aims to investigate the relationship between dietary patterns and blood sugar control in elderly patients with type 2 diabetes mellitus at the Belimbing Health Center in Padang City in 2025. This type of research is Observational analytic with cross-sectional research design. This research was conducted at Belimbing Health Center Padang City on March 19 - April 12, 2025. The population in this study were elderly people with type 2 DM who visited the Belimbing Health Center Health services with a sample of 86 people taken by accidental sampling technique. Data analysis used is univariate and bivariate analysis. Data processing using computerization. Dietary patterns were measured using questionnaires FFQ and blood sugar levels were measured by observing patients' medical records. The results showed 55.8% of respondents had a poor diet, 95.3% of respondents had uncontrolled blood sugar values. This study shows that there is a relationship (0.01 <0.05) between diet and blood sugar control in elderly people with type 2 DM in the Belimbing Health Center Working Area, Padang City. It is expected that health center officers who hold the Diabetes Mellitus program to remind people with type 2 Diabetes Mellitus, about the importance of dietary management in controlling blood sugar levels so that it can help in controlling blood sugar